Analisis Perbandingan Metode Replikasi Server untuk Kebutuhan Pemulihan Bencana (Studi Kasus Sistem Informasi Geografis Perusahaan XYZ) - Ulfa Khoirul Azizah; Ismiarta Aknuranda; Widhi Yahya (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
XYZ Company is one of the largest oil companies in the world, operating in more than 130 countries. To maintain its business process activities, XYZ company uses one of application called GIS Portal Mahakam. This application is installed on a conventional server in Balikpapan Base. To protect critical business processes from catastrophic failures, which can result in the loss of a company's ability to conduct business processes normally, XYZ companies undertake disaster recovery planning or DRP. In the implementation of DRP required process to replicate the GIS application server to Sepinggan Datacenter Recovery Center (DRC). There are three methods that support the replication server, namely the physical to physical, physical to virtual vmware converter, and physical to virtual baremetal restore. This study was conducted to compare selected replication methods, with the aim of obtaining the best replication methods to be applicable in the DRP process. The research data was obtained based on result of interview and observation. There are three methods of analysis performed. First, a comparison analysis of replication methods on the network side, storage, servers and operating systems, and applications. Second, the analysis of replication method using business impact analysis (BIA). Third, analysis of pros and cons on each replication method. Based on research that has been done, physical to virtual vmware converter method has maximum tolerable downtime for 1.375 days with the highest pros.